ANALISIS TERPUTUSNYA KONEKSI REMOTE CONTROL SWITCHING UNIT (RCSU) PADA PERALATAN MIDDLE MARKER MEREK SELEX - Prasojo, Muhamad Adimukti; Toni; Utama, M. Kukuh Darma (Spektral, 2023)
The Instrument Landing System (ILS) is one of the flight navigation equipment that functions to provide guidance signals to aircraft in the final approach position towards the runway. ILS consists of three components: Localizer, Glide Path, and Marker Beacon. To facilitate monitoring of its equipment, ILS has a monitoring software called the Remote Control Switching Unit (RCSU). RCSU is used to provide a central visual monitoring station with information about the status of ILS, DVOR, and DME equipment. RCSU is connected to each ILS shelter. This research aims to find a solution to the disconnection issue of the RCSU Middle Marker of the Selex brand. The research method used is qualitative data collection through descriptive data analysis techniques and data collection through semi-structured interviews and participative observation. The method starts with equipment checking, analysis, and problem resolution. Through this research, it was found that the cause of the issue was a damaged RJ 45 connector due to corrosion. The corrosion was caused by rainwater and temperature fluctuations in the surrounding environment.